Breast Health Problems Are Rare in Both HIV-Infected and HIV-Uninfected Women Who Receive Counseling and Support for Breast-Feeding in South Africa. - (:unkn) unknown (My University, 2007)
Background. Breast problems, including mastitis, can interfere with the duration and exclusivity of breast-feeding. However, there are no large prospective studies documenting the prevalence, duration, and timing of such problems in breast-feeding women, particularly those who are infected with human immunodeficiency virus (HIV).Methods. Women enrolled prenatally underwent a breast-feeding counseling intervention until 6 months after delivery. Breast health problems were documented per breast for 180 days after delivery, with 14-day recall histories.Results. Breast health problems were rare, and there were no significant differences between HIV-infected and HIV-uninfected women for any of the following conditions: engorgement, 39 HIV-infected women (3.5%) versus 33 HIV-uninfected women (2.7%; P=.30); breast thrush, 17 (1.5%) versus 12 (1.0%; P=.25); bleeding nipple, 6 (0.5%) versus 4 (0.3%; P=.45); and mastitis/abscess, 11 (1.0%) versus 6 (0.5%; P=.17). Most problems occurred during the first month after birth, with few additional mothers experiencing problems after this point: at 1 and 6 months, 13% and 17% of all mothers, respectively, had experienced a minor or major breast health problem, including sore nipples. Women who had not exclusively breast-fed their infants were more likely to experience any of the breast health problems than were women who had exclusively breast-fed their infants (time-dependent variable; adjusted odds ratio, 1.46; 95% confidence interval, 1.13-1.87; P=.003). HIV-infected women who experienced any serious breast health problem (i.e., bleeding nipple, pus oozing from a nipple or breast, or mastitis/abscess) were 3.55 times (95% confidence interval, 0.86-14.78 times; P=.08) more likely to transmit HIV postnatally to their infant.Conclusions. With encouragement to exclusively breast-feed, women experienced few breast health problems. When those problems did occur, HIV-infected women with bleeding nipple, pus oozing from a ni
Keywords: African Research